Medical Tourism in the Philippines: Trends, Challenges, and Opportunities from a Decade of Literature Review - Reyes, Jon Paul; Castillo, Stephanie (Journal of Interdisciplinary Perspectives, 2025)
Medical tourism refers to patients traveling abroad to access affordable and high-quality healthcare. This industry has grown quickly in Asia, with the Philippines emerging as a potential hub due to its skilled workforce, competitive prices, and cultural connections to foreign markets. However, compared to regional leaders such as Thailand, India, and Malaysia, the Philippine medical tourism sector remains underdeveloped. There is a noticeable gap in research, as previous studies have not provided a thorough overview of the trends, challenges, and opportunities in the country’s medical tourism sector. To address this, a systematic narrative review was conducted in accordance with PRISMA guidelines. It covered literature published from January 2015 to September 2025 across databases such as PubMed/MEDLINE, Scopus, Web of Science, Embase, Google Scholar, and HERDIN, as well as government and industry reports. Out of 1,352 screened records, 59 studies met the inclusion criteria. These included 32 empirical papers, 15 policy analyses, and 12 reviews. The findings showed a growing demand for affordable care, an increase in services aimed at the diaspora, and the rise of telemedicine for ongoing treatment before and after care. Ongoing challenges included fragmented governance, a lack of international accreditation, workforce migration, and pandemic-related disruptions. However, there are opportunities in niche markets like dental care, cosmetic surgery, wellness, and retirement healthcare. Overall, while the Philippines has significant potential to become a strong player in medical tourism, its progress depends on improving accreditation, governance, retaining healthcare workers, and investing in digital health. Strategic coordination and policy integration are essential to achieving sustainable, fair growth in this developing sector.